2022
DOI: 10.3390/foods11223618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Volatile Composition and Sensory Behavior of Habanero Pepper during Lactic Acid Fermentation by L. plantarum

Abstract: Habanero pepper is recognized for its appealing aroma and flavor. Lactic acid fermentation can improve these sensory properties, especially aroma, by the synthesis of volatile compounds, which might also increase the consumer preference. Thus, the aim of this research was to compare the volatile composition as well as different sensory parameters such as preference and emotions related to the lactic acid fermentation of Habanero pepper by two strains (wild and commercial) of Lactiplantibacillus plantarum. A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition, it is a technique to preserve food and has unique sensory attributes [ 134 ]. Several studies have been conducted with chili paste fermented with different strains of lactic acid bacteria and yeasts [ 134 , 135 , 136 , 137 , 138 , 139 ]. However, most of these studies have studied the effect on the sensory attributes produced by fermentation [ 135 , 136 , 137 , 138 ] or monitoring of the microorganisms during autochthonous chili fermentation [ 139 ].…”
Section: Incorporation Of Polyphenols and Capsacinoids From ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is a technique to preserve food and has unique sensory attributes [ 134 ]. Several studies have been conducted with chili paste fermented with different strains of lactic acid bacteria and yeasts [ 134 , 135 , 136 , 137 , 138 , 139 ]. However, most of these studies have studied the effect on the sensory attributes produced by fermentation [ 135 , 136 , 137 , 138 ] or monitoring of the microorganisms during autochthonous chili fermentation [ 139 ].…”
Section: Incorporation Of Polyphenols and Capsacinoids From ...mentioning
confidence: 99%
“…Several studies have been conducted with chili paste fermented with different strains of lactic acid bacteria and yeasts [ 134 , 135 , 136 , 137 , 138 , 139 ]. However, most of these studies have studied the effect on the sensory attributes produced by fermentation [ 135 , 136 , 137 , 138 ] or monitoring of the microorganisms during autochthonous chili fermentation [ 139 ]. Consequently, further studies are needed to study the effect of fermentation on bioactive compounds (mainly phenolic compounds).…”
Section: Incorporation Of Polyphenols and Capsacinoids From ...mentioning
confidence: 99%
“…The gallery plot shows that the distinct flavor profile of VOCs mainly pertains to acids and alcohols among the groups. A total of 48 VOCs were characterized in all samples, which were divided into six categories, namely, aldehydes (4), acids (4), ketones (8), esters (11), alcohols (12), and others (9).…”
Section: Gc-ims Analysismentioning
confidence: 99%
“…As one of the main microorganisms in fermented peppers, lactic acid bacteria (LAB) have the ability to produce various VOCs through carbohydrate metabolism, amino acid catabolism, and fatty acid metabolism and, in turn, leads to the unique flavor of various fermented peppers [ 10 ]. López-Salas et al found that consumers preferred Habanero pepper fermented with commercial or wild Lactobacillus plantarum ( L. plantarum ) compared to unfermented ones, and the fermented product showed significantly higher levels of VOCs, such as 1-hexanol, cis -3-hexenyl hexanoate, and 3,3-dimethylhexan-1-ol [ 11 ]. Moreover, a previous study suggested that Lactobacillus , the dominant microbiota in salted fermented peppers, was positively correlated with the contents of valencene, hexyl acetate, and toluene, and these compounds conferred fruity, floral, and woody aromas to products [ 12 ].…”
Section: Introductionmentioning
confidence: 99%